A corpus-based analysis of learners’ spelling and morpho-syntactic writing errors and mistakes. Case study of senior secondary schools in Brazzaville (Congo) - Rodrigue Lézin ALLEMBE (Ilmu Inovasi Nusantara, 2022)
This research work aimed at identifying and analyzing errors and mistakes that Congolese EFL learners commit in their written productions with regard to spelling and morpho-syntax aspects. We carried out the investigation in two senior secondary schools: Réconciliation and Kintélé, located in Brazzaville. To obtain reliable results, we used for data collection the EFL learners’ copies from grade 3 of these two schools of our choice. Besides, we used the descriptive analytical method and Corder’s errors analysis theory (EA) to identify and analyze the types of errors and mistakes made in writing. The results show that EFL learners mostly make interlingual errors (interference between French and English) at the level of selection (morphological and grammatical errors) and of syntax (misordering of words). To enhance EFL learners’ writing skills, we suggest some strategies and techniques teachers should use during writing instruction